El aprendizaje de las matemáticas por medio de la solución de problemas. - García Retana, José Ángel (2009)
The “algorithm” generally used in orimary and secondary education for the solution of problems in Mathematics consists of three stages: conceptualization and formulation of the problem, operations and results. This resource enhances the product over the process; due to this it is partial, insufficient, emphasizing, learning without understanding. In this context, we propose a more detailed and complex “algorithm” that could favour an increased and more effective learning from a constructivist and comprehensive perspective. The solution of problems can favour assuming a conscience (metacognitive action) that will facilitate both teachers and students to direct in a more efficient way the learning process.